Characterization, Phytochemical Screening of Phyllanthus emblica L. Fruit Nanoherbal and Determination of the Estrus Cycle of Female Rats - Nurul Suci; Masfria; Aminah Dalimunthe; Hafid Syahputra (International Journal of Science, Technology & Management, 2023)
One of a plant that is thought to have quite high antioxidant activity is kemloko (Phyllanthus emblica L.). This plant is a material that is often used by the community as a traditional medicine. This plant in India has been used to treat cancer, diabetes, liver (liver), heart problems and anemia. This biological activity is thought to be caused by the presence of bioactive compounds from secondary metabolites contained therein, especially compounds from the phenolic and flavonoid groups. The short length of the estrus cycle of rats makes them ideal for investigation of changes occurring during the reproductive cycle. The estrus cycle lasts four days and is characterized as: proestrus, estrus, metestrus and diestrus, which may be determined according to the cell types observed in the vaginal smear. Since the collection of vaginal secretion and the use of stained material generally takes some time, the aim of the present work was to provide researchers with some helpful considerations about the determination of the rat estrus cycle phases in a fast and practical way. This study began with macroscopic examination, examination of water content, examination of water-soluble extract levels, examination of ethanol-soluble extracts, examination of total ash content, and also an examination of acid-insoluble ash levels, phytochemical screening of Phyllanthus emblica L. fruit nanoherbal and determination of the estrus cycle of female rats. The results of phytochemical screening showed that the compound of Phyllanthus emblica L. Fruit nanoherbal contained a class of secondary metabolites of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. And the estrus cycle of female rats can be determined by observing changes in vaginal epithelial cells.